Prediction of the severity of acute urticaria in children, taking into account the type of autonomic dysfunction - L. A. Averkina; A. N. Posevina; S. V. Maltsev; A. A. Lebedenko (Медицинский вестник Юга России, 2024)
Objective: to study the features of the inﬂuence of the autonomic nervous system on the severity of acute urticaria in children.Materials and methods: 73 children with acute urticaria were examined. Clinical research methods included an analysis of the life history and illness, an objective examination of the child, and recording of a cardiointervalogram.Results: clinical and anamnestic data made it possible to identify features of the course of the disease that were not previously noted before the development of urticaria, such as complaints of pain in the heart, a feeling of diﬃculty breathing (without the presence of concomitant quincke's edema), dizziness, increased sweating (mainly of the palms and soles); analysis of the initial autonomic tone in children with acute urticaria; in cases of mild disease, a pronounced predominance of eutonia is observed, which indicates a coordinated increase in the activity of both the sympathetic and parasympathetic parts of the autonomic nervous system, and in patients with a pronounced clinical picture, a noticeable predominance of vagotonia is recorded.Conclusion: The created model for predicting the severity of acute urticaria, taking into account clinical and anamnestic parameters, as well as changes in the functioning of the autonomic nervous system, makes it possible to more objectively assess the severity of this pathology.